Optimization of the Preventive Potential of Andaliman (Zanthoxylum acanthopodium DC) as a Natural Biofilter Against Cigarette SmokeExposure Through TNF-α Expression - Novidawati Boru Situmorang; Andy Febriady (Jurnal FARMASIMED (JFM), 2025)
Background: Indonesia ranks third in the world for the highest smoking prevalence after China and India. Smokers often smoke both indoors and outdoors, exposing others to harmful cigarette smoke. Cigarette smoke can trigger oxidative stress, which induces the release of pro-inflammatory cytokines such as Tumor Necrosis Factor (TNF-α). Objective: This study aimed to analyze the optimization of andaliman (Zanthoxylum acanthopodium DC) as a natural biofilter against cigarette smoke exposure through TNF-α expression as a potential preventive measure. Methods: An experimental method was used by measuring TNF-α expression in serum isolated from mice blood using the Enzyme-Linked Immunosorbent Assay (ELISA) technique. Results: TNF-α levels measured by ELISA showed that andaliman extract at doses of 50–400 mg/kg body weight significantly reduced TNF-α levels in mice exposed to cigarette smoke compared to the negative control group (p < 0.05). This reduction is likely related to the presence of flavonoids and alkaloids in andaliman, which act as antioxidants and immunomodulators that inhibit inflammatory pathways triggered by oxidative stress from cigarette smoke. With its anti-inflammatory potential, andaliman can be developed as an eco-friendly natural biofilter to prevent the harmful effects of cigarette smoke, although further studies are needed regarding its optimal dosage and long-term safety. Conclusion: Andaliman extract (Zanthoxylum acanthopodium DC) effectively reduced TNF-α levels in mice exposed to cigarette smoke, demonstrating anti-inflammatory potential as a natural biofilter. Its flavonoid and alkaloid content act as antioxidants and immunomodulators that suppress inflammatory pathways induced by cigarette smoke toxins. Andaliman shows promise as an environmentally friendly natural preventive agent to mitigate the negative impacts of cigarette smoke exposure.